2021
DOI: 10.1007/s12298-021-01046-7
|View full text |Cite
|
Sign up to set email alerts
|

Short term UV-B radiation mediated modulation of physiological traits and withanolides production in Withania coagulans (L.) Dunal under in-vitro condition

Abstract: Accumulation of secondary metabolites is a key process in the growth and development of plants under different biotic/abiotic constraints. Many studies highlighted the regulatory potential of UV-B treatment towards the secondary metabolism of plants. In the present study, we examined the impact of UV-B on the physiology and secondary metabolism of Withania coagulans , which is an important ayurvedic plant with high anti-diabetic potential. Results showed that in-vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 78 publications
(99 reference statements)
2
6
0
Order By: Relevance
“…As the final decomposition product of lipid peroxidation and due to the combined mechanisms above, MDA contents reflect the lipid peroxidation level and cellular lipid peroxidation damage to a certain extent ( Zeng et al, 2019 ). Our results were similar to those of other research ( Tripathi et al, 2021 ), short-term UV radiation significantly enhanced the anti-oxidant enzyme systems. Other studies ( Li et al, 2019 ) showed that with further stress, the peroxidation of the membrane system was enhanced, and the MDA content increased.…”
Section: Resultssupporting
confidence: 93%
“…As the final decomposition product of lipid peroxidation and due to the combined mechanisms above, MDA contents reflect the lipid peroxidation level and cellular lipid peroxidation damage to a certain extent ( Zeng et al, 2019 ). Our results were similar to those of other research ( Tripathi et al, 2021 ), short-term UV radiation significantly enhanced the anti-oxidant enzyme systems. Other studies ( Li et al, 2019 ) showed that with further stress, the peroxidation of the membrane system was enhanced, and the MDA content increased.…”
Section: Resultssupporting
confidence: 93%
“…In fact, NaCl stress increased the expression of enzymes involved in the biosynthesis of withanolides, causing an increase in the accumulation of these medicinal compounds in leaves. Similar results of increased accumulation of withanolides under cold stress [ 52 ] and UV-B radiation [ 17 ] have been previously documented. It has been reported that secondary metabolites are involved in improving the adaptation of plants under stressful conditions, so the increase in the accumulation of withanolides can indicate the induction of defense mechanisms in order to improve the adaptation of plants during NaCl stress [ 9 ].…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies have shown that the biosynthesis of secondary metabolites is influenced by abiotic and biotic elicitors [ 11 ]. Recently, it has been shown that the use of different elicitors has an effect on the accumulation of withanolides in W. coagulans [ 17 ], W. somnifera [ 18 ], and Physalis peruviana [ 19 ] plants. However, there is no reports on the interaction effects of ML with abiotic stresses as two important elicitors of withanolide accumulation in W. somnifera .…”
Section: Introductionmentioning
confidence: 99%
“…Literature review denoted both increased, decreased or sometimes unchanged Ci concentration in UV‐B‐exposed plants such as in Withania coagulans , Curcuma caesia , C. longa , Paubrasilia echinata and Oryza sativa (12,21,46,47). Therefore, low stomatal conductance and transpiration were reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics are the products of phenylpropanoid pathway and extensively studied under UV exposure. Several studies have reported both increase and decrease in alkaloids, terpenes and phenolics (12,(17)(18)(19)(20)(21)(22). Among several groups of compounds studied, only few studies have been so far conducted on plants having saponin content.…”
Section: Introductionmentioning
confidence: 99%